EVALUASI PENGALAMAN PENGGUNA DALAM DESAIN PERANGKAT LUNAK BERBASIS MULTIMEDIA - Mahdi, Prayuda Zaky Al; Teguh Darma Pinandhita; Muhamad Ainul Yaqin (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2025)
The achievements and implementation of modern information technology currently have an impact on various aspects of life, for example through multimedia software applications. For example, the KAI Access application as a means of ordering train tickets online, although it has an efficient system, still requires in-depth evaluation related to User Experience (UX) for the impact of effectiveness and user satisfaction. The purpose of this study is to evaluate the user experience of the KAI Access application using the User Experience Questionnaire (UEQ). UEQ has six dimensions: attraction, clarity, efficiency, accuracy, stimulation, and novelty. This study uses a quantitative method with a UEQ questionnaire structure contained in 26 core issue questions to 35 respondents. Among the results obtained, in terms of acquisition, this application received a satisfactory score on the dimensions of accuracy, stimulation, and novelty; attraction still needs to be improved, but performance on efficiency and clarity has decreased. This study offers a better interface design in order to significantly improve the holistic user experience. Keywords: user experience, KAI Access, User Experience Questionnaire, multimedia, software evaluation.